Association between urinary phthalate levels and chronic pain in US adults, 1999–2004: A nationally representative survey - Jin, Guoping; Nie, Yaoyao; Fan, Jiayao; Yang, Ye; Chen, Dingwan; Li, Yingjun; Ju, Li (Frontiers in Neurology, 2023)
Chronic pain has been a public health concern throughout the world. Ascertaining and managing its risk factors helps develop well-directed treatment plans and prevention strategies. Phthalates exposure leads to various health problems. The present study aims to explore the potential correlation between urinary phthalate metabolites and chronic pain in adults in National Health and Nutrition Examination Survey (NHANES) from 1999 to 2004 in the US. Seven urinary phthalate metabolites were examined and analyzed. As a result, the chronic pain prevalence reached 52.19% (n=2,138) among the participants, and females account for a large proportion (57.75% vs. 42.25%). After multivariable logistic regression analysis, a higher prevalence of chronic pain was observed among participants in the third tertile of mono-(2-ethyl)-hexyl phthalate (MEHP) (OR=1.23, 95% CI=1.02-1.48, P=0.034) and mono-benzyl phthalate (MBzP) (OR=1.28, 95% CI=1.04-1.58, P=0.022) in our adjusted model. The log-transformed concentration of MBzP also showed a significant association with chronic pain prevalence (OR=1.09, 95% CI=1.01-1.18, P=0.036) in the adjusted model. For further analysis, the positive correlations of unary phthalate metabolites with chronic pain remained robust when stratified by gender and chronic pain site. In brief, our findings firstly presented a positive correlation between urinary phthalate metabolites and chronic pain among adults participants, and more causal researches should be conducted to ascertain the interactions and to expound their underlying mechanisms.